Analyzing the conditions, potentials, and trends of vegetation biodiversity in conservation zones located within the business license area of PT PHE Ogan Komering - Jun Harbi; Heripan Heripan; Noril Milantara; Henri Yuwono; Suharyadi Suharyadi; Romi Romantik; Indra Sundara Alhusna; Muhammad Abdul Latif Al-Ansori (Journal of Global Sustainable Agriculture, 2024)
Utilization of natural biological resources and their ecosystems responsibly and sustainably can be achieved through environmental management efforts, such as conservation. One company undertaking such efforts is PT Pertamina Hulu Energi Ogan Komering (PHE OK), which manages a conservation area. This research involves observations in the conservation area to obtain current data (conditions and potential) and trends at the location, in order to formulate strategies for its protection and management. The study was conducted in the PHE OK conservation area in Peninjauan Village, Peninjauan District, Ogan Komering Ulu Regency, South Sumatra Province. Data and analysis were performed using vegetation analysis methods, resulting in several parameters, including Density (K), Relative Density (KR), Frequency (F), Relative Frequency (FR), Dominance (D), Relative Dominance (DR), Importance Value Index (INP), Dominance Index (ID), Margalef Species Richness Index (R), Shannon Diversity Index (H'), and Pielou Evenness Index (E). The analysis results show a positive trend, with an increase in biodiversity values from low in 2022 to moderate currently. Additionally, the R value for seedling level is moderate, while it is low for saplings, poles, and trees. The E value for seedlings, saplings, poles, and trees all fall into the high species richness category. There has been an increase in each biodiversity indicator value compared to 2022, indicating that the protection efforts thus far have produced positive outcomes. However, more extensive enrichment is needed to achieve a significant increase in biodiversity